The efficacy of human papillomavirus vaccination in young Japanese girls: the interim results of the OCEAN study. Issue 1 (31st January 2022) - Hiramatsu, Kosuke; Ueda, Yutaka; Yagi, Asami; Morimoto, Akiko; Egawa-Takata, Tomomi; Nakagawa, Satoshi; Kobayashi, Eiji; Kimura, Toshihiro; Kimura, Tadashi; Minekawa, Ryoko; Hori, Yumiko; Sato, Kazuaki; et al.
ABSTRACT: Human papillomavirus (HPV) vaccine has been used to prevent chronic HPV infection, which accounts for cervical cancer. Japanese Ministry of Health, Labor and Welfare (MHLW) conducted an HPV vaccination campaign in 2010 and the Obstetrical Gynecological Society of Osaka initiated a multicenter, prospective cohort study in Osaka, Japan – OCEAN (Osaka Clinical resEArch of HPV vacciNe) study – to investigate the oncogenic HPV prevalence and the long-term protection rate of HPV vaccine. A total of 2814 participants were enrolled on their visit for HPV vaccination between 12 and 18 years old. Among them, 102 participants received HPV/Pap co-test as primary cancer screening at the age of 20–21. We compared the prevalence in two groups (the vaccinated and the unvaccinated group). HPV infection ratio was significantly lower in the vaccinated group compared to the unvaccinated (12.9% vs. 19.7%; p = .04). In particular, HPV 16 and 18 were not detected in the vaccinated group, while 4.9% of participants in the unvaccinated group were infected ( p = .001), suggesting that vaccination provided effective protection against high-risk types of HPV. The cross-protection effect of HPV vaccines was also observed against HPV 31, 45, and 52. Although HPV vaccines were not contributed to the reduction of cervical intraepithelial neoplasia 1 (CIN) ( p = .28), CIN2 or worse was not observed in vaccinated group. Our research showed that at the age of 20–21, HPV vaccine inhibited the infection of high-risk HPV and had impacted on the development to CIN2 or worse in Japan.